A covering model application on Chinese industrial hazardous waste management based on integer program method. (April 2015) - Li, Lei; Wang, Shi; Lin, Yanting; Liu, Wenting; Chi, Ting
Abstract: Industrial hazardous waste is a special kind of toxic substance, which poses risks to the environment as well as human health. With the speeding up of industrialization in China, the collecting, recycling, treatment and disposal of industrial hazardous waste gradually become a severe problem to both the environmental protection and the resource management. In this paper, we laid an emphasis on prospective optimization, used integer program method, and selected the optimal locating approach to the collecting and handling of industrial hazardous waste on the basis of covering location model. We also selected an industrial intensive district in Hebei Province in China as an empirical object and examined our model result. Compared to previous results, this one bears the characteristics of immediacy, dynamism and predictability.